MAPPING RESEARCH TRENDS IN GAME-BASED ICT LEARNING FOR INTERACTIVE EDUCATIONAL APPLICATIONS: A BIBLIOMETRIC STUDY - Suryani, Epi; Bentri, Alwen; Hendri, Nofri; Rayendra, Rayendra; Prasetia, Anggi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The rapid growth of digital technology in the education sector requires effective and innovative information and communication technology (ICT) solutions to enhance student engagement and support interactive learning. This study aims to analyse existing research patterns, collaborative structures, central themes, and future research opportunities in the field of game-based ICT learning. A bibliometric assessment was conducted using publications indexed in Scopus published between 2021 and 2025. The data were examined using VOSviewer to examine the co-occurrence of keywords, collaborative networks among authors, and the structural themes of the research. The findings indicate a significant increase in academic literature on game-based ICT learning, underscoring a strong focus on factors such as learning motivation, student engagement, digital literacy, and the development of 21st-century competencies. The study of visual depictions categorises three main research areas: the development of game-centred educational applications, the adoption of interactive digital instructional methods, and the measurement of educational outcomes. The uniqueness of this study lies in the provision of an extensive bibliometric mapping that explains the development of research themes on immersive technology and the integration of artificial intelligence in educational applications. These empirical results make a substantial contribution to the field of educational technology research by providing evidence-based insights for the design of learner-centred adaptive digital learning environments, while also directing future research toward a sustainable implementation framework and measurable impact on students' digital competencies and educational outcomes.